Intellectual Capital and Company Performance Moderated by Board of Directors Characteristics - Fayola, Berlynn; Fu, Morgan; Rijanto, Arief; marsetio, nany chandra (Universitas Muhammadiyah Malang, 2024)
Purpose: This study aims to determine the effect of intellectual capital (IC) on company performance. In addition, this study also examines the role of board characteristics as moderation of intellectual capital on firm performance. Methodology/approach: The sample consists of 140 non-financial companies listed on IDX during 2015–2019. The data analysis technique used in this research is panel data regression analysis. Findings: The results show that intellectual capital is able to affect the company's performance on ROA, ROE, and TQ. Board characteristics through the Education Level and Board Size proxy are found to not be fully capable of moderating the relationship between IC and firm performance, while the gender proxy is found to be unable to moderate the relationship between IC and company performance. Practical implications: The efficiency of intellectual capital can have an impact on improving the company's performance. The characteristics of the board become an important factor that strengthens the influence of IC on improving the company's performance. Originality/value: The research contribution is measuring the effect of IC on market-based company performance. Furthermore, adding the effects of corporate governance that are measured by board characteristics as moderating variables strengthens the relationship between IC and company performance.